A data-driven synthesis of research evidence for domains of hearing loss, as reported by adults with hearing loss and their communication partners - Vas, Venessa; Akeroyd, Michael A.; Hall, Deborah A. (SAGE, 2017)
A number of assessment tools exist to evaluate the impact of hearing loss, with little consensus among researchers as to either preference or psychometric adequacy. The item content of hearing loss assessment tools should seek to capture the impact of hearing loss on everyday life, but to date no one has synthesized the range of hearing loss complaints from the perspectives of the person with hearing loss and their communication partner. The current review aims to synthesize the evidence on person with hearing loss- and communication partner-reported complaints of hearing loss. Searches were conducted in Cos Conference Papers Index, the Cumulative Index to Nursing and Allied Health Literature, Excerpta Medica Database, PubMed, Web of Science, and Google Scholar to identify publications from May 1982 to August 2015. A manual search of four relevant journals updated the search to May 2017. Of the 9,516 titles identified, 78 records (comprising 20,306 participants) met inclusion criteria and were taken through to data collection. Data were analyzed using meta-ethnography to form domains representing the person with hearing loss- and communication partner-reported complaints of hearing loss as reported in research. Domains and subdomains mutual to both perspectives are related to ‘‘Auditory’’ (listening, communicating, and speaking), ‘‘Social’’ (relationships, isolation, social life, occupational, and interventions), and ‘‘Self’’ (effort and fatigue, emotions, identity, and stigma). Our framework contributes fundamental new knowledge and a unique resource that enables researchers and clinicians to consider the broader impacts of hearing loss. Our findings can also be used to guide questions during diagnostic assessment and to evaluate existing measures of hearing loss.